Caracterização do queijo colonial da microrregião de Francisco Beltrão - PR e estudo com consumidores - Steinbach, Juliana (2017)
Milk production, very strong in the region, has been growing significantly in recent years. More than 50% of the milk produced is destined to the manufacture of cheeses, a fact that makes this product the most relevant of the agroindustries of Sudoeste Paranaense. Traditionally, the colonial cheese is very present and accepted by the local population, being produced by half of the cheese industries of the region, and very often it is manufactured of artisan form, which illustrates its socioeconomic importance. Despite its regional relevance, there are few data on this cheese, there being no standard of identity and no legislation about it. The objective of this work was to characterize the colonial cheese by quantitative descriptive analysis, to evaluate its acceptance and to draw a profile of consumers, correlating the data with the physical and chemical characteristics of the product. Samples of 5 dairy products from the Francisco Beltrão - PR microregion were evaluated, being three under municipal inspection, and three under state inspection regimen. The physical chemical characterization of the colonial cheese demonstrated the lack of standardization of the product, with great variation even between the batches of the same dairy. Colonial cheese can be classified as a medium-moisture cheese, or semi-hard dough, and like a fatty cheese. In the microbiological analyzes it was verified a high count of thermotolerant coliforms, due to the use of raw milk in the process or inadequate pasteurisation. The results obtained in the Quantitative Descriptive Analysis - ADQ were expressed by means of Principal Component Analysis (ACP) and spider graphic, which indicated bitter and slightly pungent taste, a considerable amount of eyesight, with a very uniform mass, besides taste and odor Moderate acids. In the consumer tests the colonial cheeses had good acceptability and positive attitude towards the purchase. In the study of the consumers it was verified that although the most consumed cheese is the mozzarella cheese, the consumers demonstrated to prefer the colonial cheese in relation to the others.